Effect of different periods of hyperbaric oxygen on ischemia-reperfusion injury of rat small bowel - Bertoletto,Paulo Roberto (2008)
PURPOSE: To determine whether hyperbaric oxygen (HBO) could effectively protect the small intestine mucosa against an ischemic insult, according to different periods of application. METHODS: The gut of 32 male rats was subjected to 60-min ischemia (clamping the mesenteric artery and vein); After they were further reperfused upon clamp opening during 60 min. Animal groups were as follows. GII = placed on HBO during the ischemia period; GIII = placed on HBO during reperfusion; GIV = treated with HBO throughout the ischemia-reperfusion period. Some animals (GI) did not receive HBO treatment at all and served as reference of ischemia-reperfusion injury (IR). HBO was carried out in a cylindrical acrylic chamber (2.0 ATA). Samples of small bowel were prepared for H.E staining for histological evaluations. RESULTS: The histological injury of mucosa was significantly less when HBO was administered during the ischemia period (17.6 ± 0.6) as compared with the IR (21.3 ± 1.8). HBO was not effective when applied during reperfusion (23.1 ± 2.1) or during the ischemia plus reperfusion period (18.7 ± 1.9). The thickness of the mucosa was preserved by HBO in ischemia (327.50 ± 30.23 µm) in comparison with the IR (172.79 ± 5.95 µm). In the periods of reperfusion (162.50 ± 6.05 µm) and ischemia plus reperfusion (296.49 ± 20.01 µm) the mucosa revealed a structural injury. CONCLUSION: Hyperbaric oxygen affects the ischemic insult of small bowel, being the favorable effect obtained when hyperbaric oxygen was administered early in the ischemic period.